(3agQS JgPjH GdceGd aj CSeGA GdQLGds - (3jhSa Hf YHO GdQMef Hf jhSa, CHh GdMLGL, LeGd GdOjf GHf GdRcj CHj eMeO GdbVGYj GdcdHj GdeRj,J (B742 (3g` s ((3EHQGgje Hf YHO Gddg Hf TQa GdOjf CHh GdMSf s)
(3ChdgG (B:s
(3GdMeO ddg GdPi CfGQ WQjb GdMb hCHGf SHd GdgOi CeG HYO aEf Gddg JYGdi hdg GdMeO de jNd GdCQV ef bGFe dg s
(3BNQgG (B:s
(3jfJgi HJQLeI YHO Gdedc hLjH GdCROi s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B8 - (3U (B236 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B13 - (3U (B308s
Keywords: (3GdJGQjNs